Pendidikan Kesehatan tentang Minuman Seduhan Jahe untuk Mengatasi Emesis Gravidarum pada Ibu Hamil Trimester I di PMB Yustati Ambarita - Tiwi, Laida Sanilpa; Arifarahmi, Arifarahmi; Nurbaiti, Nurbaiti (Universitas Baiturrahim, 2024)
In the first trimester of pregnancy, there are several complaints or discomforts during pregnancy which disrupt the pregnant woman's activities. These complaints are often experienced during early pregnancy, namely morning sickness or emesis gravidarum. Changes due to the estrogen hormone during pregnancy will result in excessive stomach acid, causing nausea in the morning. Emesis gravidarum can cause a decrease in appetite which results in changes in the balance of electrolytes such as sodium, calcium and potassium, causing changes in the body's metabolism. Complementary therapy to reduce emesis gravidarum can use herbal plants, including ginger. Ginger contains the essential oils zingiberena (zingirona), zingiberol, bisabilena, curcumin, gingerol, flandren, vitamin A and bitter resin which can block serotonin in the neurotransmitter which is synthesized in serotonergic neurons found in the central nervous system and enterochromaffin cells in the digestive tract so that it can provide a taste. comfortable in the stomach so it can overcome nausea. The aim of the community service activity is to provide education about ginger brewed drinks to treat emesis gravidarum for pregnant women in the first trimester. This activity was carried out on June 13 2023 at PMB Yustati Ambarita. The implementation method is lecture, discussion and question and answer. The media used is in the form of leaflets. As a result of this activity, pregnant women already know about ginger brew to treat emesis gravidarum by consuming 250 mg of ginger brew, taken 2-4 times a day for a week.